2011
DOI: 10.1021/cg101308r
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Small Molecule Additives and Chemical Modification in Protein Crystallization

Abstract: An alternative approach to promoting the crystallization of proteins is to enhance intermolecular contacts between macromolecules or to eliminate intermolecular interactions or interactions with solvent that might inhibit crystallization. Site-specific mutations have been employed, as have truncations by genetic or proteolytic means. There are, however, significant problems. Because the structure of the target macromolecule is unknown, there may be no good basis for the design of mutants or truncations. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 33 publications
(64 reference statements)
2
39
0
1
Order By: Relevance
“…Interestingly, the calorimetric approaches, discussed above, arrived at the same conclusion . This is in line with the working hypothesis tested by Alex McPherson, according to which additives promote crystallization by enhancing intermolecular contacts between proteins or by removing such contacts between proteins or solvent .…”
Section: Crystallogenesis In the Era Of Technologies And Structural Gsupporting
confidence: 75%
“…Interestingly, the calorimetric approaches, discussed above, arrived at the same conclusion . This is in line with the working hypothesis tested by Alex McPherson, according to which additives promote crystallization by enhancing intermolecular contacts between proteins or by removing such contacts between proteins or solvent .…”
Section: Crystallogenesis In the Era Of Technologies And Structural Gsupporting
confidence: 75%
“…Since the pioneering studies on additive effects on protein crystal growth [36,46,47], the use of these molecules has become extremely widespread. In the literature many papers discuss the action and the effects of these substances on the protein crystallizability and very recently McPherson et al have suggested that these small reagents, and their combinations, may play a primary role in the crystallization process [35]. …”
Section: Factors Affecting Crystallization Of Bio-macromoleculesmentioning
confidence: 99%
“…[103,104]). Here we are primarily interested in methods that modify very specific patches to achieve the potential for cohesive interactions, driving the formation of crystal contacts.…”
Section: Target Protein Modification For Enhanced Crystallizabilitymentioning
confidence: 99%